Biopolitics or Biolinguistics? On language and human nature (With Some Glosses on Agamben and the “sovereign power”) - Cimatti, Felice (Rivista Italiana di Filosofia del Linguaggio)
The thesis of this paper is that “biopolitics” in fact means biolinguistics. More specifically, the thesis is that biopolitics – defined as the grip of political power on the human body and life – is but a consequence of the main biological character of Homo sapiens: language. Politics (economics) and religion are but consequences of the basic anthropological fact that human beings are primarily speaking beings, that is, the animals of language. Therefore, from an anthropological perspective the intrinsically biolinguistic nature of human animals is the ground of biopolitics. Every form of dualism (body on one side, psyche, Power, and God on the other) derives from the original dualistic structure of language. In the last part of this paper, an analysis of Agamben’s thought about language will argue in favor of this thesis